PEMBELAJARAN BIPA DI UNIVERSITAS MUHAMMADIYAH JAKARTA LEVEL 1: AKTIVITAS HARIAN - Irma Dwi Arianti, Irma (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2024)
Indonesian Language Learning for Foreign Speakers (BIPA) is an educational process that focuses on teaching Indonesian to individuals who are not native speakers. This research uses a qualitative method in which the presentation and interpretation of data is structured based on descriptive form, which means that the results of this research are in the form of quotations and words. The aim of this writing is to improve your listening, speaking and sentence composing skills in Indonesian. Learning activities are designed to encourage active learners, enrich vocabulary, and understand the cultural context in everyday use of Indonesian. By utilizing technology and online media, it aims to facilitate interactive and interesting learning.